Analysis of Students' Entrepreneurial Motivation and Responses Based on Entrepreneurship-Oriented Project-Based Learning - Fitriani, Salsabila; Solfarina, Solfarina; Wijayanti, Imas Eva (Universitas Sultan Ageng Tirtayasa, 2024)
An effective and valid learning device for chemoentrepreneurship-based projects was produced for solve the one of many problems learning in Indonesia, especially about environment-managed thinking skill. This is important to optimize to increasingly explore education during senior high school and to earn a living after graduation. By this research, we can be overcome by STEM-integrated project-based learning on the topic of environmental management in the form of teaching materials and chemoentrepreneurship oriented. This research aimed to produce chemistry teaching materials: ecological management based on project-based learning-oriented chemoentrepreneurship. This research was developed using the method Analyze, Design, Develop, Implement, and Evaluate shortened to ADDIE model and using 8 expert validators to provide validation of material and media content. The results of the research showed that the validation of materials and media was declared valid because the Vcount obtained was 0.90 exceeding 0.75 in the Aiken's test. As well as 90% declared that the device is feasible to use to learn. This statement is reinforced by the results of 63 students as responses who studied at an islamic senior high school were used for limited testing. They said that this new device of teaching materials obtained a percentage of 90% and was categorized as very good for study material about entrepreneurship-based environments.